The Role of Sport in Physical Education in Finland and the Kurdistan Region of Iraq—Primary School Teachers’ Reflections - Joonas Kalari; Warhel Asim Mohammed; Golaleh Makrooni; Pål Lagestad (Education Sciences, 2025)
There is a lack of studies comparing PE teachers’ reflections on the role of sport in different regions. Using Kirk’s conceptualization of the role of sport, this qualitative comparative study aimed to explore and compare fifth-grade physical education (PE) teachers’ perceptions and experiences related to PE teaching in Finland and in the Kurdistan region of Iraq (KRI). In-depth interviews were conducted with eight Finnish and six KRI teachers, and the data were analyzed using the NVivo qualitative analysis program. The results showed that the Finnish teachers’ reflections were classified into four themes: joy and competence rather than sport, sport and curriculum, the status of sport in society and prerequisites for physical activities and sport. The KRI teachers’ reflections were also classified into four themes: sport as an aim in PE, the teacher as a model and leader of the sport, sport raising one’s status and PE being not only about sport. The role of sport in PE was recognized by teachers from both regions, although from different perspectives. The Finnish teachers made a clear distinction between PE and sport. The KRI teachers perceived PE and sport almost as one, in the belief that PE primarily teaches pupils about sport and that sport itself is a central goal. Both groups of teachers aimed to enhance their pupils’ well-being and encourage a physically active lifestyle through PE. The KRI teachers believed that engaging students in sports would promote these aims, whereas Finnish teachers saw sport as just one of many components needed to achieve these objectives. The Finnish teachers emphasized the national PE curriculum guiding their work, while the KRI teachers had no standardized PE curriculum in primary school. This comparative study highlights the importance of implementing a well-structured PE curriculum in primary schools in the KRI. Further studies should examine how the implementation of such a curriculum will affect KRI teachers’ teaching and the role of sport in PE.